Hybrid Elastic Organic Crystals that Respond to Aerial Humidity - Lan, Linfeng; Yang, Xuesong; Tang, Baolei; Yu, Xu; Liu, Xiaokong; Li, Liang; Naumov, Panče; Zhang, Hongyu (Angewandte Chemie International Edition, 2022)
Reshaping of elongated organic crystals that can be used as semiconductors, waveguides or soft robotic grippers by application of force or light is now a commonplace, however mechanical response of organic crystals to changes in humidity has not been accomplished yet. Here, we report a universal approach to instigating a humidity response into elastically bendable organic crystals that elicits controllable deformation with linear response to aerial humidity while retaining their physical integrity entirely intact. Hygroresponsive bilayer elements are designed by mechanically coupling a humidity‐responsive polymer with elastic molecular crystals that have been mechanically reinforced by a polymer coating. As an illustration of the application of these cladded crystalline actuators, they are tested as active optical transducers of visible light where the position of light output can be precisely controlled by variations in aerial humidity. Within a broader context, the approach described here provides access to a vast range of mechanically robust, lightweight hybrid hygroresponsive crystalline materials. A new class of lightweight, mechanically reinforced, hygroresponsive organic crystalline hybrid materials has been synthesized by a universally applicable approach. The crystals are robust, durable, and moisture‐absorbing, and show a highly linear deformation over a wide range of relative humidity. Such precise spatiotemporal control over the light output in response to air humidity allows the materials to be used as optical waveguides.